Quantification of Antinuclear Antibodies (IgG) Existence in General Population of Pakistan - Atif Amin, Baig; Salman, Amiruddin; Ahmad Zubaidi, A.latif; Nordin, Simbak (2018)
The autoimmune disorders and auto antibodies are rapidly becoming a major cause of concern in the medical field. Antinuclear antibody plays a significant role in autoimmunity and it is targeted against different nuclear antigens. Although its elevated levels are found in autoimmune disorders but it is also synthesizedin healthy individuals. To find out its incidence a number of studies have been conducted on healthy individuals of various populations but limited data is available about the frequency of auto antibodiesin Pakistan. Blood samples of 587 (503 females and 84 males) individuals were taken through convenience sampling technique. Serum was separated by centrifugation and then ANA titer was determined by Enzyme Linked Immunosorbent Assay (ELISA). SPSS version 20.0 (IBM-SPSS, Inc, Armonk, New York) was used for statistical calculations.ANA autoantibodies were found only in 6 individuals,out of which 5 were females and 1 was male. No significant association of antinuclear antibodies was observed between males and females. Evaluation of the incidence of ANA in general population is important to ensure its reliability as a biomarker of disease. Current study found very low occurrence of ANA in general population, which indicates its exclusive association with the diseases especiallyautoimmune diseases. The one percent positive cases can be further followed up for being at risk of developing disease.